The strength of Muhammadiyah's existence in the modern era: Pillars of empowerment and community strengthening - Wahyu Prihanta; Moh. Nurhakim; Saiful Amien (Journal of Community Service and Empowerment, 2024)
A study regarding the role of Muhammadiyah in the pillars of community empowerment and strengthening needs to be carried out, considering that this organization is the largest organization in Indonesia. This article aimed to analyze the strength of Muhammadiyah's existence which focuses on the pillars of empowerment and strengthening of society. This paper was prepared using library research methods. Data were analyzed using qualitative descriptive analysis. Data visualization, especially regarding references and keywords that frequently appear, is assisted with VOSviewer. The results show that Muhammadiyah is an Islamic organization that has a clear and real role in empowering and strengthening of society. Muhammadiyah has a central role in the field of philanthropy, in fact this has become Muhammadiyah's identity. Al-Ma'un became the ideological-theological foundation of Muhammadiyah's struggle. The advocacy movement through community empowerment has changed the face of Muhammadiyah to become more populist. Community empowerment is carried out through action programs that directly touch on the real problems of poor and marginalized communities represented by farmers, fishermen, livestock breeders, workers, urban poor communities and people with disabilities. Women's groups who have been marginalized and tend to be subordinated have also become targets of empowerment work carried out by Muhammadiyah, especially through its wing organization, namely Aisyiyah.